محاسبة القيمة العادلة في شركات التأمين ( دراسة تطبيقية) - فلوح, صافي; حسن, عيسى هاشم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
بدأ الاهتمام في السنوات الماضية يتزايد بتطبيق مفهوم القيمة العادلة لقياس أصول و التزامات المنشأة بما فيها أصول والتزامات عقود التأمين، لما يوفره من معلومات مالية تتمتع بخاصية الملاءمة والموثوقية وقابلية المقارنة. وقد أصدر مجلس معايير المحاسبة الدولية العديد من المعايير التي تعتمد القيمة العادلة لقياس أصول والتزامات المنشأة بشكل عام، وطرح مؤخراً موضوع اعتماد القيمة العادلة لتقييم أصول والتزامات عقود التأمين. وإن إلزام شركات التأمين المدرجة في سوق الأوراق والأسهم المالية السورية باعتماد معايير المحاسبة الدولية يطرح إشكالية تطبيق مفهوم القيمة العادلة لتقييم أصول والتزامات شركات التأمين السورية لما لهذا المفهوم من أهمية. In recent years, the application of the concept of fair value to measure assets and liabilities of the facility, including assets and liabilities of insurance contracts gained a lot of interest. This is for the wealth of financial information which has the feature of convenience, reliability and comparability. International Accounting Standards Board has issued many standards based on fair value to measure assets and liabilities of the facility in general, and it introduced recently the idea of adopting the fair value assessment of assets and liabilities of insurance contracts. And forcing insurance companies listed on the stock and stock Syrian adopting international accounting standards is a problematic application of the concept of fair value to assess the assets and liabilities of the Syrian insurance companies.